Building Xperience: a multilevel alcohol and drug prevention intervention. - Diamond, Sarah; Schensul, Jean J; Snyder, Leslie B; Bermudez, Alessandro; D'Alessandro, Nicole; Morgan, Damion Sincere (American journal of community psychology, 2009)
"Xperience" is an innovative alcohol and drug prevention program that has adopted a multilevel, community-based strategy to promote drug-and-alcohol free social activities, venues and norms among urban youth ages 14-20. The intervention aims to strengthen protective factors and reduce risk factors for alcohol and other substance use among high school age youth by addressing multiple factors at the individual, peer, community and city level. The purpose of this paper is to discuss the process of building the different levels of this intervention during the 3-year formative phase. We will explain: (1) Why we chose to adopt a multilevel and participatory strategy, (2) Formative research leading to the intervention model, (3) The theoretical framework underlying the methodology, (4) Pilot intervention development (Years One and Two), (5) Current program methods and outcome goals, and lastly, (6) Some of the lessons learned, goals achieved, and plans for the future. This descriptive account of building a multilevel intervention aims to serve as a useful guide for others wishing to develop similar approaches, and for theorizing about some of the common challenges involved in this process.
Keywords: Adolescent; Adult; Alcohol Drinking; Community Mental Health Services; Female; Humans; Male; Social Marketing; Substance Abuse Treatment Centers; Substance-Related Disorders; Urban Population; Young Adult